2022
DOI: 10.1029/2022ja030828
|View full text |Cite
|
Sign up to set email alerts
|

A Parametric Study of Oxygen Ion Cyclotron Harmonic Wave Excitation and Polarization by an Oxygen Ring Distribution

Abstract: OCH waves are electromagnetic emissions with discrete spectral peaks at or near the harmonics of the oxygen ion cyclotron frequency. These waves were observed by the Akebono satellite inside the plasmasphere (L = 1.5-2.5) (H. Liu et al., 1994), by Van Allen Probes outside the plasmasphere (Usanova et al., 2016;Yu et al., 2017), and by the Magnetospheric Multiscale (MMS) mission inside the plasma sheet boundary layer (Usanova et al., 2018). A statistical study based on Van Allen Probes showed that OCH waves occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Harmonic waves with frequencies below the proton gyrofrequency have been reported by many studies in the past few years (Chen et al, 2018;Deng et al, 2022;Liu et al, 2020Liu et al, , 2022Min et al, 2017;Usanova et al, 2016Usanova et al, , 2018Wang et al, 2022;Yu et al, 2017;Zhu & Chen, 2019). Some studies found that EMIC waves can generate harmonics through the nonlinear process (Chen et al, 2018;Deng et al, 2022;Sauer & Dubinin, 2022;Yao et al, 2020;Yu et al, 2021;Zhu & Chen, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Harmonic waves with frequencies below the proton gyrofrequency have been reported by many studies in the past few years (Chen et al, 2018;Deng et al, 2022;Liu et al, 2020Liu et al, , 2022Min et al, 2017;Usanova et al, 2016Usanova et al, , 2018Wang et al, 2022;Yu et al, 2017;Zhu & Chen, 2019). Some studies found that EMIC waves can generate harmonics through the nonlinear process (Chen et al, 2018;Deng et al, 2022;Sauer & Dubinin, 2022;Yao et al, 2020;Yu et al, 2021;Zhu & Chen, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Linear analysis and hybrid simulations have demonstrated that OCH waves are excited by hot oxygen ion distributions with a positive slope along the perpendicular velocity direction, that is, ∂ f /∂ v ⊥ > 0, where f is the distribution function and v ⊥ represents the velocity perpendicular to the background magnetic field (K. Liu et al., 2020; X. Liu et al., 2022; Min et al., 2017; Pokhotelov et al., 1997). The waves correspond to the oxygen ion Bernstein modes in kinetic theory, and the maximum wave growth rates occur at quasi‐perpendicular propagation, similar to the proton Bernstein modes related to MS waves (Chen & Thorne, 2012; Gary et al., 2010, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Such a latitudinal distribution of OCH waves is similar to that of fast magnetosonic (MS) waves, although the occurrence rate of OCH waves is much smaller than that of MS waves. Linear analysis and hybrid simulations have demonstrated that OCH waves are excited by hot oxygen ion distributions with a positive slope along the perpendicular velocity direction, that is, ∂f/∂v ⊥ > 0, where f is the distribution function and v ⊥ represents the velocity perpendicular to the background magnetic field (K. Liu et al, 2020;X. Liu et al, 2022;Min et al, 2017;Pokhotelov et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…In the past few years, harmonic waves with frequencies below the proton gyrofrequency have been studied by many researchers (e.g., Chen et al., 2018; Deng, Yuan, Huang, et al., 2022; K. Liu et al., 2020; X. Liu et al., 2022; Min et al., 2017; Usanova et al., 2016, 2018; Xue, Yuan, Yu, Deng, & Huang, 2022; Yao et al., 2020; Yu et al., 2017, 2021; Zhu & Chen, 2019). Some of these harmonics are considered to be oxygen ion harmonic waves which have the same spectral and propagation properties as EMIC waves, i.e., transverse electromagnetic waves and propagation with a direction almost parallel to the background magnetic field (Usanova et al., 2016, 2018).…”
Section: Introductionmentioning
confidence: 99%